The Dynamic Process of Life Satisfaction - Heller, Daniel; Watson, David; Ilies, Remus (Journal of personality, 2006)
ABSTRACT Drawing from the Cognitive Affective Personality System (Mischel & Shoda, 1995, 1998), we argue for a need to examine within‐individual variation in life satisfaction. Thus, employing a diary study of 76 fully employed, married adults we examined the magnitude, antecedents, and consequences of intra‐individual variation in life satisfaction. Our findings establish a substantial amount of intra‐individual variation, comparable to other personal evaluations assessed with a state approach (e.g., self‐esteem), but less than that observed with major mood dimensions. In addition, concurrent changes in life satisfaction were systematically related to fluctuations in job and marital satisfaction; however, contrary to prediction, our results did not support a cross‐level moderating role of Neuroticism in these associations. Our findings also lend support for the lagged influence of life satisfaction on next‐day domain satisfaction ratings. Taken together, our findings demonstrate the systematic nature and importance of within‐subject variation in life satisfaction.